2016
DOI: 10.1194/jlr.m068205
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of perilipin 3 into a glycero(phospho)lipid monolayer depends on lipid headgroup and acyl chain species

Abstract: function of LDs. While much work has focused on peripheral and integral membrane proteins, the mechanism by which LD binding proteins recognize and target to LDs is still poorly understood (1). This is especially true for dedicated LD binding proteins of the perilipin family, i.e., perilipin 1 through 5, that function in the biogenesis and metabolism (lipolysis) of LDs. No work has directly investigated the interaction of a perilipin family member with a phospholipid monolayer interface. In order to address ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 78 publications
(101 reference statements)
1
24
2
Order By: Relevance
“…It is also interesting that a strong protein-lipid interaction is observed with the ordered (gel phase) DPPC, whereas the protein has very limited binding affinity with the liquid disordered (fluid phase) DOPC phospholipid. While structural data on PLIN1 is still lacking, functional studies suggest that both PLIN2 and PLIN3 contain independent, non-overlapping, lipid-binding sites involving the 11-mer amphipathic helical motif that is common to all perilipins, including PLIN1 32 , 33 . PLIN1 additionally has a hydrophobic motif that mediate lipid droplet targeting independently 34 .…”
Section: Resultsmentioning
confidence: 99%
“…It is also interesting that a strong protein-lipid interaction is observed with the ordered (gel phase) DPPC, whereas the protein has very limited binding affinity with the liquid disordered (fluid phase) DOPC phospholipid. While structural data on PLIN1 is still lacking, functional studies suggest that both PLIN2 and PLIN3 contain independent, non-overlapping, lipid-binding sites involving the 11-mer amphipathic helical motif that is common to all perilipins, including PLIN1 32 , 33 . PLIN1 additionally has a hydrophobic motif that mediate lipid droplet targeting independently 34 .…”
Section: Resultsmentioning
confidence: 99%
“…How the perilipin family members recognize and target to lipid droplets with specific lipid content and whether interactions with the surface phospholipid monolayer direct perilipin targeting remain largely unanswered questions, although a recent study has revealed that the acyl chain saturation of phospholipids affects the interaction of recombinant truncated forms of perilipin 3 with phospholipid monolayers of varying composition in vitro (6). To date, few studies have addressed the biophysics of the phospholipid and protein surface properties of lipid droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid packing and membrane curvature promote AH recruitment through creation of lipid packing defects, which have been analyzed extensively in bilayer membranes 18 20 . It is not clear which parameters are important for AH binding to the LD surface 21 . A recent in silico analysis suggests that whereas an LD phospholipid monolayer at zero surface tension does not behave very differently from a bilayer, lipid packing defects increase non-linearly with increasing surface tension of the monolayer 22 .…”
Section: Introductionmentioning
confidence: 99%